Study of human pepsinogen polymorphism by combining chromatographic and electrophoretic methods - Majercáková, P; Kucerová, Z (Sbornik lekarsky, 2001)
A new combination of chromatographic and electrophoretic methods has been developed for better separation and characterization of human pepsinogens. Pepsinogens isolated from the gastric mucosa of patients with gastric cancer have been separated using fast-protein liquid chromatography (FPLC) on an ionex Uno-Q1 column. Proteolytic active fractions were firstly immunodetected by monoclonal antibodies against PGA and PGC using ELISA and then separated by isoelectric focusation in the acidic pH 2.5-5 gradient with an excellent resolution. The combination FPLC and ELISA followed by IEF enabled to separate ten pepsinogen isoforms. This technique is very suitable for studies of the pepsinogen polymorphism and its role in the gastric diseases.
Keywords: Isoelectric Focusing; isoelektrická fokusace; Electrophoresis, Polyacrylamide Gel; Enzyme-Linked Immunosorbent Assay; lidé; Pepsinogens; ELISA; pepsinogeny; elektroforéza v polyakrylamidovém gelu; Chromatography, Liquid; Polymorphism, Genetic; nádory žaludku; Stomach Neoplasms; chromatografie kapalinová; polymorfismus genetický; Humans